Service Quality Dimension and Its Importance for Indonesia Health Care Provider Improvement - Yosie William Iroth; Gallena Sinaga, Judith Tagal; Valentine Siagian (CV. AFDIFAL MAJU BERKAH, 2024)
Access to healthcare is basic human right as highlighted by WHO and adopted into law in many countries including Indonesia. The law may not specified specific standard of quality of care that need to come with the accessibility of the care it self, but it call for ease of access and ease of care. Indonesia established a KARS or accreditation body for hospital in 1995 to help hospital to maintain their standards. Hospitals by nature are embarking on social mission to improve the quality of health of people, although from the survivability of hospital the commercial aspects need be included in the equation. Hospital like other business institutions have adopted business strategy process into their organization in order to ensure their survivability and to some organization to comply to regulatory requirements. Approach such as Balanced Scorecard and service quality are very common in organizations including in Hospitals. The purpose of this qualitative research will look at how the healthcare service providers perceive the importance of service quality to be adopted into their balanced scorecard strategy. Insights from Interviews with the healthcare providers indicates that healthcare providers are focusing service quality as part of their balanced scorecard. This insight ensures that while healthcare providers fights for their survival in the mid of rising healthcare cost, demand of better and fair care service quality dimension is still at the core of their strategy.